Taxonomy of the Proisotoma complex. V. Sexually dimorphic Ephemerotoma gen. nov. (Collembola: Isotomidae) - Potapov, Mikhail; Kahrarian, Morteza; Deharveng, Louis; Shayanmehr, Masoumeh (Zootaxa, 2015)
A new genus is proposed based on a new species from Iran, Ephemerotoma skarzynskii gen. et sp. nov., and three known species: E. huadongensis (Chen, 1985) comb. nov., E. multituberculata (Martynova, 1971) comb. nov. and E. porcella (Ellis, 1976) comb. nov. The genus shares the characters of Subisotoma Stach and Proctostephanus Börner and is distributed in southern areas of Eurasia (Eastern Mediterranean, Iran, Tajikistan, China). Ephemerotoma gen. nov. belongs to the Proisotoma-complex and is characterized by a simple maxillary palp, only 4 guards on labial papilla E and 2 prelabral chaetae. Four s-chaetae on Abd.V are arranged in two rows, two anterior and two posterior chaetae. All members of Ephemerotoma gen. nov. are redescribed or discussed based on type or fresh material, and a key to species of the genus is given. Scutisotoma potapovi Xie & Chen, 2008 is considered a synonym of E. huadongensis, while Proisotoma anopolitana is moved to the genus Proctostephanus. Sexual dimorphism is described for three species.